Analisis Pengaruh Pendidikan Dan Pelatihan Terhadap Tingkat Pemahaman Akuntansi Sektor Publik pada Badan Pengelolaan Keuangan dan Aset Daerah (BPKAD) Kota Bima NTB - Titian Khairat; Maslichah Maslichah; Dwiyani Sudaryanti (Universitas Islam Malang, 2023)
This study aims to determine the effect of education and training on the level of understanding of public sector accounting. The population in this study were employees of the regional financial and asset management agency (BPKAD) Bima City, NTB. The population in the study were 70 employees of the Regional Financial and Asset Management Agency of the City of Bima, NTB. This study uses saturated sampling, where members of the population are used as samples. The data used is primary data. While the analysis technique used is multiple linear regression analysis. The result of this study is that education and training simultaneously affect the level of understanding of public sector accounting. While partially education and training affect the level of understanding of public sector accounting.Keywords : Education, training and level of understanding of public sector accounting